CAUSAL ANALYSIS OF CORRUPTION PRACTICES AND RESISTANCE TO THE IMPLEMENTATION OF ANTI-CORRUPTION POLICIES IN GOVERNMENT INSTITUTIONS - Salsabila, Assytha; Septika Putri, Ira; Romdoni, Muhamad (Sriwijaya Crimen and Legal Studies, 2025)
This study analyzes the causal relationship between corruption practices and resistance to the implementation of anti-corruption policies within government institutions in Indonesia. The research stems from the ongoing prevalence of corruption among government officials despite the existence of comprehensive legal frameworks, revealing weaknesses in law enforcement, legal interpretation, and societal legal culture. The theoretical foundation integrates Jack Bologna’s GONE Theory with Lawrence M. Friedman’s Legal System Theory, emphasizing the interplay of legal structure, substance, and culture. Employing a qualitative normative juridical method, this study relies on secondary data derived from statutory regulations, legal journals, and case documentation to examine the legal norms governing corruption eradication. Data collection was conducted through literature review and legal interpretation techniques. The findings reveal that internal factors such as greed and materialistic behavior, combined with external factors including weak political accountability, ambiguous legal norms particularly in Articles 2 and 3 of the Anti-Corruption Law and deficient supervision, significantly hinder the effectiveness of anti-corruption policies. Furthermore, the persistence of a permissive legal culture normalizing bribery reinforces systemic resistance to reform. The study concludes that strengthening the integrity of law enforcement, refining ambiguous legal provisions, and fostering public legal awareness are essential to overcoming resistance to anti-corruption initiatives and achieving good governance in Indonesia.